SISTEM PENDUKUNG KEPUTUSAN SIMPAN PINJAM UPK MENGGUNAKAN MEDTODE AHP (Analitycal Hierarchy Process) (Universitas Sains dan Teknologi Komputer Semarang, 2022)
UPK is an Activity Management Unit formed by the Inter-Village Deliberation (MAD) to manage Community Direct Assistance (BLM) – KDP funds which can be allocated for various types of activities which include educational facilities/infrastructure, health facilities/infrastructure, UEP, and SPP ( revolving fund). To be able to provide objective assessment results to each applicant for assistance by considering the assessment criteria including group management, group member meetings, business ownership, members' economic conditions, capital structure growth, member loan arrears, management capacity in administration and finance, management capacity savings and loans, profit conditions or SHU, financial planning, the amount of group savings. The decision support system for applying for savings and loans at UPK XYZ uses the AHP (Analytical Hierarchy Process) method, which is to create a hierarchical structure of several elements used, starting with general elements, followed by sub-elements. Some of the elements used in this method include group management, group member meetings, business ownership, members' economic conditions, capital structure growth, member loan arrears, management capacity in administration and finance, management capacity in savings and loan management, profit or SHU conditions, financial planning, group savings amount. The use of the AHP method in the SPK for saving and loan applications can be applied using a web-based programming language using the MySql database. Keywords: SPK, AHP, UPK.